Investigation of the Noticing Levels of Teachers about Students’ Mathematical Thinking: A Lesson Study Model - Gülşah Özdemir Baki, Ahmet Işık (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2018)
The purpose of the study is to investigate the noticing levels of six teachers about students’ mathematical thinking. The four of teachers participated in the lesson study professional development process, and the rest did not participate in the process of lesson study. Nearly two months after the lesson study implementations were completed with the participant teachers, these six teachers were asked to write a report to evaluate the teaching process after they would watch the video recorded lessons. The data collection tools of this case study were the video recordings which the participants watched, participants’ evaluation reports and unstructured interviews. The theoretical framework developed by van Es (2011) was used to interpret the effects of lesson study process on the teachers’ noticing levels towards their students’ mathematical thinking. The findings showed that the noticing levels of the teachers, who participated in the lesson study process, appeared to be higher than the non-participant teachers. The findings also showed that lesson study professional development process increased teachers’ noticing levels on students’ mathematical thinking.